Evaluating The Effectiveness of Contraceptive Counseling in Adolescents : A Systematic Review - I Komang Sutama Arta; Agus Indra Yudhistira Diva Putra (The International Journal of Medical Science and Health Research, 2026)
Introduction: Adolescent unintended pregnancy remains a global public health challenge with significant medical and social consequences. Contraceptive counseling interventions vary widely in content, delivery, and effectiveness. This systematic review evaluates the effectiveness of contraceptive counseling interventions for adolescents on contraceptive use and pregnancy outcomes. Methods: A systematic review was conducted following PRISMA guidelines. We screened studies based on predefined criteria: target population (adolescents aged 10-19 years), intervention type (contraceptive counseling delivered by healthcare providers, trained counselors, or peer educators), effectiveness outcomes (contraceptive knowledge, attitudes, uptake, adherence, or reproductive health outcomes), and study design (randomized controlled trials, quasi-experimental studies, or controlled before-and-after studies). Data extraction included study characteristics, population details, intervention components, comparator groups, and quantitative outcomes. Synthesis focused on patterns of effectiveness across intervention types, settings, and populations. Results: Eighty studies were included, representing diverse populations across multiple countries with sample sizes ranging from 50 to over 105,000 participants. Immediate postpartum contraceptive counseling significantly increased long-acting reversible contraception (LARC) use (OR 3.78, 95% CI 2.18-6.57). Motivational interviewing interventions improved effective contraception use (OR 2.04, 95% CI 1.47-2.83) and LARC initiation (OR 3.99, 95% CI 1.36-11.68). Sustained, intensive programs like Prime Time demonstrated persistent effects at 24 months on consistent hormonal contraception use (adjusted RR 1.30) and condom use (RR 1.57). Quality initiatives removing access barriers increased LARC use by 90% and reduced teenage pregnancy rates by 36% (from 2.2% to 1.4%, p<0.0001). Peer education showed variable effectiveness, succeeding when addressing social norms but failing when reduced to information transmission. Technology-based interventions demonstrated mixed results. Discussion: Effective interventions share common characteristics: delivery during critical transition periods (particularly postpartum), sustained contact over time, motivational interviewing approaches addressing ambivalence, removal of access barriers through same-visit provision, and system-level provider training. Setting-specific barriers fundamentally shape success, with school-based health centers providing on-site contraception achieving higher uptake than referral-dependent models. Adolescents demonstrate strong preferences for implants over intrauterine devices, suggesting counseling should address method-specific concerns. Implementation challenges in real-world replications highlight the difficulty of maintaining program fidelity at scale. Conclusion: Contraceptive counseling effectively improves adolescent contraceptive use and reduces pregnancy rates when interventions are appropriately timed, sustained, and combined with structural supports. Recommendations include implementing counseling during postpartum periods, utilizing motivational interviewing techniques, ensuring same-day contraceptive access, providing system-level provider training, and addressing population-specific barriers. Future research should focus on implementation strategies that maintain effectiveness when scaling interventions.